Oxidative Stress and Antioxidant Status in Women with Polycystic Ovary Syndrome (PCOS): Stres Oksidatif dan Status Antioksidan pada Wanita dengan Sindrom Ovarium Polikistik (PCOS) - Masar Hadi Ismail; Naseer Hafedh Ibrahim; Huda Abdul Hameed Abdulrahman; Osama A. Mohsein (Academia Open, 2025)
General Background: Polycystic Ovary Syndrome (PCOS) is a prevalent endocrine disorder linked to metabolic and reproductive disturbances, where oxidative stress has been increasingly implicated. Specific Background: Evidence suggests that an imbalance between reactive oxygen species (ROS) and antioxidant defenses may contribute to the pathophysiology of PCOS, but inconsistencies in findings highlight the need for further clarification. Knowledge Gap: Despite recognition of oxidative stress in PCOS, limited studies in Middle Eastern populations have comprehensively assessed both oxidative markers and antioxidant status in relation to clinical features. Aim: This study aimed to evaluate oxidative stress levels and antioxidant defenses in Iraqi women with PCOS compared to healthy controls, and to investigate correlations with clinical and biochemical parameters. Results: Findings revealed significantly elevated oxidative stress markers (MDA, NO, AOPP) and reduced antioxidant levels (SOD, GPx, CAT, TAC) in PCOS patients, with strong correlations between redox imbalance and BMI, LH/FSH ratio, hirsutism, and acne severity. Novelty: This study provides region-specific evidence of impaired antioxidant defense in PCOS, highlighting oxidative stress as a critical mediator of symptom severity. Implications: These results underscore the potential for antioxidant-based interventions as adjunct therapies in managing metabolic and reproductive complications of PCOS.Highlight : PCOS women show increased oxidative stress and reduced antioxidants. Oxidative stress links with BMI, hormones, and clinical symptoms. Antioxidant imbalance plays a role in PCOS pathogenesis Keywords : Polycystic Ovary Syndrome (PCOS), Oxidative Stress, Antioxidant Status, Reactive Oxygen Species (ROS), Inflammation